The first protocol for assessing the welfare of dromedary camels (Camelus dromedarius) kept under nomadic pastoralism - Padalino, Barbara; Menchetti, Laura (Frontiers in Veterinary Science, 2024)
There is no protocol to measure the welfare level of dromedary camels (Camelus dromedarious) kept under pastoralism -the predominant husbandry system of this species. This study therefore aimed to develop and describe a protocol for measuring welfare levels in dromedary camels kept under nomadic pastoralist conditions-. The indicators for each welfare principle (i.e. Good Feeding, Good Housing, Good Health, and Appropriate Behavior) were tailored to the specific conditions of camel pastoralism, drawing from the currently available protocol for assessing welfare in dromedary camels kept in intensive and semi-intensive systems. This adaptation was achieved using a structured literature search and Expert Knowledge Elicitation (EKE). The developed protocol, covering animal-, resource-, and management-based indicators, comprises two assessment levels: 'Caretaker-Herd level' and 'Animal level'. The Caretaker-Herd level is a face-to-face interview of about 10 minutes including 16 questions, spit into the four welfare principles, and a visual observation of applied animal handling practices. The 'Animal level' encompasses a behavioral observation and a visual clinical inspection of randomly selected individual dromedary camels, about 5 minutes/camel. The 'Animal level' includes 27 welfare indicators displayed for each welfare principle. The present study also includes the score for each indicator, the model for aggregating indicators' scores into compound indices for each welfare principle (PAI), and how to classify the herds based on the PAIs or to produce an overall welfare index for each herd. Even if the proposed protocol needs to be applied, refined, and validated, it is a first step towards a standardized method to collect data related to dromedary camel welfare kept under pastoralism. This framework may ultimately guide herd managers, animal health practitioners, experienced advisers, and lawmakers in fostering optimal conditions and proposing welfare standards for dromedary camels in pastoralist settings.